Frequencies of Gag-restricted T-cell escape "footprints" differ across HIV-1 clades A1 and D chronically infected Ugandans irrespective of host HLA B alleles. Issue 14 (30th March 2015) - Serwanga, Jennifer; Nakiboneka, Ritah; Mugaba, Susan; Magambo, Brian; Ndembi, Nicaise; Gotch, Frances; Kaleebu, Pontiano
Highlights A and D infected subjects even though they bear the same presenting HLA alleles, and live in the same environment. Escape mutations that are known to confer survival advantage were more frequent in clade A-infected subjects irrespective of host HLA alleles. There was no evidence to link this difference in outcome to the evaluated adaptive T-Cell responses (IFN-γ responses and polyfunctional responses) to those key structurally constrained Gag epitopes. However, we have demonstrated that there was significantly greater selective pressure on the Gag protein of clade A than that of clade D. The data are in line with the known faster disease progression in clade D than clade A infected individuals. The data also highlight that the current difficulties in formulating a global HIV vaccine design will be further challenged by clade associated differences in outcome.